2011
DOI: 10.1007/s11694-011-9114-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of an experimental procedure for real time investigation of diffusion in foods

Abstract: Diffusion and mass transfer are ubiquitous operations in food processing. The application of electric fields can influence the mass transfer properties of foods. A small scale processing unit was used in the development of a method that would allow real-time measurement of diffusion of dyes into gel samples (at a range of temperatures and electric field strengths). The depth of penetration and localisation of infused material can be visualised and measured using image analysis methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Erioglaucine disodium salt, with a molecular formula of C 37 H 34 N 2 Na 2 O 9 S 3 , was used as a diffusing substance in the experiments. According to Samprovalaki et al 58 who used the diffusion imaging method to study diffusion in hydrogels, the sensitivity of conversion from the gray to concentration value increases with decreasing concentration of the dye solution because at a higher concentration, the fluctuation of the gray value produces larger errors when the system is saturated. Therefore, in the present experiments, the concentration of erioglaucine disodium salt was fixed at 0.2 mg/mL, which had been calibrated to ensure accuracy of the diffusion imaging method.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Erioglaucine disodium salt, with a molecular formula of C 37 H 34 N 2 Na 2 O 9 S 3 , was used as a diffusing substance in the experiments. According to Samprovalaki et al 58 who used the diffusion imaging method to study diffusion in hydrogels, the sensitivity of conversion from the gray to concentration value increases with decreasing concentration of the dye solution because at a higher concentration, the fluctuation of the gray value produces larger errors when the system is saturated. Therefore, in the present experiments, the concentration of erioglaucine disodium salt was fixed at 0.2 mg/mL, which had been calibrated to ensure accuracy of the diffusion imaging method.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For example, mass transfer was enhanced when MEF were applied to the infusion of synthetic colorants in potato, potato-alginate mix and agar gels (Kemp and Fryer, 2007), and adsorption of bovine serum albumin to Cibracron blue Sepharose in an electrochromatographic column increased when electrical fields were applied, making mass transfer of protein in the adsorbent particles more effective (Jia et al, 2007). Diffusion of rhodamine6G and methylene blue into gels of agar and alginate when electrical fields from 0 to 667 V m À1 were applied, showed little effect on diffusion (Samprovalaki, 2005;Samprovalaki and Fryer, 2011). Meanwhile, it was suggested that the presence of MEF during preparation of chitosan coating solutions may influence their transport properties and electrical processing has been suggested as a route to modify edible films and coatings for applications such as increasing shelf life (Souza et al, 2009).…”
Section: Introductionmentioning
confidence: 99%